REVITALISASI NILAI SDGs DALAM PEMBELAJARAN IPS: PENGEMBANGAN MEDIA ULAR TANGGA BERBASIS LITERASI LINGKUNGAN - Santi Ulfi Sana; Ferani Mulyaningsih (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This research is motivated by the condition of Social Sciences (IPS) learning which tends to still focus on theoretical aspects in discussing global issues, including the Sustainable Development Goals (SDGs), so that it has not been able to provide real learning experiences for students, resulting in decreased interest in learning and learning grades. Based on this, this study aims to develop learning media in the form of a snakes and ladders game based on environmental literacy by integrating specific SDGs indicators. The method used in this study is Research and Development (R&D), which includes the stages of design, development, validation, and testing the effectiveness of the media. The results showed that the snakes and ladders media developed met the criteria. In this study, class 7B of Sirojuth Tholibin Kersan Middle School was used as the test subject. The results showed that the snakes and ladders learning media developed met the valid criteria. The validation results by material experts obtained a score of 93% and the validation results by media experts reached 93%, both of which are in the